1995
DOI: 10.1044/jshr.3803.630
|View full text |Cite
|
Sign up to set email alerts
|

Novel Word Learning in Children With Hearing Impairment

Abstract: This study examined novel word-learning abilities in young school-age children with mild-to-moderate hearing losses. We questioned whether degree of hearing loss or measures of language and phonological processing abilities were more likely to be related to novel word-learning ability. Subjects were 20 children with hearing impairment (M = 9:0) and 20 children with normal hearing (M = 6:5) matched for receptive vocabulary knowledge. Children were administered measures of language and phonological processing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
130
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 19 publications
12
130
2
1
Order By: Relevance
“…[12][13][14][15][16][17] Findings of suboptimal academic skills have been reported in school age children with mild bilateral HL. [27][28][29][30][31][32][33][34][35] Other investigators have reported delayed development of vocabulary and speech skills in children with unilateral HL. 36,37 Although it has been reported that children with unilateral rightsided HL have poorer performance on verbal tests than children with left ear unilateral HL, 16 our cohort was too small and diverse to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Findings of suboptimal academic skills have been reported in school age children with mild bilateral HL. [27][28][29][30][31][32][33][34][35] Other investigators have reported delayed development of vocabulary and speech skills in children with unilateral HL. 36,37 Although it has been reported that children with unilateral rightsided HL have poorer performance on verbal tests than children with left ear unilateral HL, 16 our cohort was too small and diverse to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Word-learning may be reduced due to the degree and configuration of hearing loss, nonoptimal hearing aid characteristics, environmental noise, reverberation, and distance from the speaker. Several studies have been conducted to determine the effect of hearing loss on word-learning in children (Gilbertson & Kamhi, 1995;Lederberg, Prezbindowski, & Spencer, 2000;. Gilbertson & Kamhi (1995), for example, investigated the production and perception of nonsense words in 5-to 9-year-old children with normal hearing and in 7-to 10-yearold children with hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to determine the effect of hearing loss on word-learning in children (Gilbertson & Kamhi, 1995;Lederberg, Prezbindowski, & Spencer, 2000;. Gilbertson & Kamhi (1995), for example, investigated the production and perception of nonsense words in 5-to 9-year-old children with normal hearing and in 7-to 10-yearold children with hearing loss. Their results revealed significantly poorer performance by the children with hearing loss for at least 3 of the 4 nonsense words presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ability to recover this time-varying spectral structure is critical to the processes involved in language acquisition, such as early word learning. In turn, that idea means that the effects of broadened auditory filters associated with hearing loss could be predicted to disrupt early word learning especially strongly, and support for that prediction comes from studies showing difficulties specifically in word learning among children with mild-to-moderate hearing loss, compared to children with normal hearing (e.g., Gilbertson and Kamhi, 1995;Stelmachowicz et al, 2004). Again, however, outcomes in those studies for children with hearing loss did not vary with degree of threshold shift, raising the possibility that the extent of broadening of auditory filters may have an effect on language acquisition somewhat independently of auditory thresholds.…”
Section: Introductionmentioning
confidence: 99%